Global, regional, and national total burden related to hepatitis B and attributable risk factors in adults aged 65 years and older from 1990 to 2021 and projection to 2030 - Gao, Linying; Ren, Yanfeng; Hu, Songyue; Zhang, Yifan; Bai, Hongjing; Li, Jinbo; Wang, Keke; Wang, Suping; Feng, Yongliang (Frontiers in Public Health, 2025)
BackgroundHepatitis B virus and its complications remain a major global public health threat. This study aimed to assess the global, regional, and national trends of total burden related to hepatitis B among older adults aged ≥65 years from 1990 to 2021 and predict trend to 2030.MethodsDrawing upon the Global Burden of Diseases (GBD) 2021, we obtained the data on incidence, prevalence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021, categorized by sex, age, and socio-demographic index (SDI). Associations of. these metrics and SDI were analyzed. Secular trends were evaluated employing average annual percentage changes (AAPC) and joinpoint regression, with future trajectories estimated through 2030 using the Bayesian age-period-cohort (BAPC) model.ResultsFrom 1990 to 2021, the global age-standardized incidence rate (ASIR) of total burden related to hepatitis B among older adults aged ≥65 years declined from 710.53 to 591.79 per 100,000 population (AAPC −0.57%), and age-standardized DALYs rate (ASDR) declined from 927.65 to 605.93 per 100,000 population (AAPC -1.39%). ASIR and ASPR both showed significant decreasing trends in males and females, with persistently higher rates observed among males across all study years. The ASIR increased only in the >95 years age group, while a significant increase in DALYs was observed across all age strata, with the magnitude of increase escalating with advancing age. ASIR increased exclusively in high SDI countries (AAPC 0.16%). In 2021, Central Sub-Saharan Africa accounted for the peak ASIR (1,671.36 per 100,000 population), conversely North Africa and the Middle East showed the most pronounced ASDR decline (AAPC -2.74%). Both alcohol use and smoking emerged as the most consequential modifiable risk factors for DALYs in adults aged ≥65 years. Projections indicate declining trends in ASIR, ASDR, and ASMR for this population by 2030, whereas ASPR is projected to exhibit an upward trend.ConclusionThe global burden and trends of total burden related to hepatitis B among older adults aged ≥65 years showed a significant decline, with projections indicating continued reduction by 2030. However, notable regional and national disparities persist. Key challenges in managing health risks for adults aged ≥65 years remain centered on alcohol use and smoking.